Tanggung Jawab Hukum Sumber Daya Manusia Potensi Basarnas Dalam Melakukan Tindakan Medis Terhadap Korban Bencana - Andrianto, Wahyu; Noviani, Nindya (Jurnal Hukum & Pembangunan, 2021)
First aid is a basic medical action that can’t be avoided by The Human Resource Potential (HR Potential) of BASARNAS during SAR Operation. Even though it is only categorized as a basic medical act, first aid can determine victims’ life because first aid is done to prevent them from getting more severe injuries or experiencing death. Despite there is no a specific regulation about basic medical action conducted by HR Potential of BASARNAS during SAR operations. This legal research focuses on answering three problems. First, how the legal rules in Indonesia regarding volunteer participation during disasters. Second, how is the authority of HR Potential for medical actions committed during the disaster. And last, how a HR Potential’s legal responsibilities in conducting medical actions against disaster victims. This research is performed using normative juridical method, the data are collected from library studies and interviews involving related respondents. The results will be presented descriptively